FINANCIAL INSTRUMENTS AUDIT PROGRAM ACCORDING TO THE INTERNATIONAL AUDITING PRACTICE STATEMENT NO. 1000 (SPECIAL CONSIDERATIONS IN FINANCIAL INSTRUMENTS AUDITING) - Milad Hilal Hamo; Prof. Dr. Khawla H. Hamdan (American Journals, 2023)
The research aims to identify the general framework of financial instruments and audit procedures in accordance with international auditing standards, and prepare an audit program to audit financial assets according to the International Auditing Practice Statement No. 1000. Special considerations in auditing financial instruments, as it provides important practical assistance to auditors when addressing the issue of evaluation and other considerations related to financial instruments. And that the auditor obtains reasonable assurance about whether the financial statements as a whole are free from material errors, whether they are caused by fraud or error, and the research has reached a set of conclusions, the most important of which are: And auditing accounts do not meet the requirements of auditing in described of the new accounting treatments described under the International Financial Reporting Standards with regard to financial instruments, and the research also reached the most important recommendations: the need to adopt the proposed auditing program that was designed by the researcher in the Federal Office of Financial Supervision and auditing and auditing companies Which shows how to audit accounts that fall within the scope of the requirements of (IFRS 9), (IFRS 7), (IAS 32) and the International Auditing Practice Statement No. (1000), as it includes clear audit procedures on each item that falls within the scope of these standards, to assist the external auditor. It can be relied upon when auditing financial assets and expected credit losses.
Keywords: audit program, financial instruments, IAPN 1000, IFRS 9, IFAC.